Narratives of the companion Ruwayfa bin Thabit (may God be pleased with him) in the nine books - an analytical study- - Arif , Hazim (Islamic Sciences Journal, 2023)
The Prophet (may God bless him and grant him peace) has conveyed to us what was revealed to him from his Lord, and he explained to the honorable Companions all the rulings of the Islamic religion, and the Companions (may God be pleased with them) in turn conveyed this great religion to those who came after them from among the followers. Perhaps one of these distinguished companions is the great companion, Ruwafa’ bin Thabit al-Ansari, whom the Prophet (peace and blessings be upon him) preached about his long life and told him that people will change after him and return to some matters of ignorance, so this great companion took it upon himself Like the rest of the Companions, people should be informed of what the Messenger of Truth and the elite of creation (may God bless him and grant him peace) told them, including the permissibility of partnership in things, especially during jihad There is a fear that the common thing will be spoiled if it is divided, and it is also clear that people will do things that people used to do in the pre-Islamic era, including wrapping the beard for the purpose of arrogance or pride, as the polytheists used to do before Islam and that God made spoils for the fighters lawful and good, but not It is permissible for a fighter to take something from the booty before it is divided.